Technical Economic Optimization Analysis for Cost-Effective Process of CNC Laser Machine G-Weike LC6090 Using Simplex Lattice – Centroid and Full Costing Methods - Tjahyono, Rudi (Institute of Research and Community Outreach - Petra Christian University, 2024)
This research focuses on the technical economic optimization of the CNC CO2 laser machine G-Weike type LC6090 for engraving acrylic material. Because there is no ideal tabulation that serves as a guide for the operator in setting machine parameters, one of the issues in operating the machine is that the engraving process for acrylic materials is still traditionally done through estimation or approximation. Indeed, this affects process inconsistency, leading to resource waste and machine operations due to defects. Since defective process results cannot be fixed or recycled, the cost of raw materials and machining will inevitably be incurred. This study emphasizes the principle of effectiveness in optimizing the laser machine-level settings for the engraving process using the Simplex Lattice-Centroid approach to generate a tabulation of optimal settings. With a speed variable level setting of 55,556 mm/s, a power of 50%, and an interval of 0.083782, the ideal results value at processing time is 1.240184, depth is 0.054967, and roughness is 0.012728. The scan speed variable strongly correlates with optimization of depth, roughness, and processing time. The scan interval variable has a moderate correlation with depth, and the power variable has a moderate correlation with processing time and roughness. The best cost efficacy in the process was then ascertained by measuring cost-effectiveness using the Full Costing method. The cost-effective results are IDR 46,778.08 per hour or IDR 13,472,087.04 annually. Using cost-effective measurements can produce a Life Cycle Cost (LCC) of the CNC laser machine value of IDR 134,720,870.4 per 10-year service lifetime.